Physical activity on mental wellbeing in senior English Premier League soccer players during the COVID-19 pandemic and the lockdown. Issue 12 (2nd December 2022) - Grimson, Sophie; Brickley, Gary; Smeeton, Nicholas J.; Abbott, Will; Brett, Adam
ABSTRACT: The COVID-19 pandemic and the subsequent lockdown created new stressors that could potentially attenuate mental wellbeing (MW) in athletes, who are already susceptible to poor MW. This study aims to describe fluctuations to MW during "lockdown" and subsequent "return to sport" protocols, in comparison to the normal "in-season" in professional soccer. Twenty-five English Premier League (EPL) soccer players completed the Warwick-Edinburgh Mental Wellbeing Scale (WEMWBS) every two weeks, during the 2019/2020 season, and every week during "lockdown" and "return to training" for 28 weeks. The duration of each physical activity (PA) session completed was recorded. No significant differences were found for MW between time points (In-season, lockdown, return to training and the restart) (51.5 ± 5.6 vs. 50.7 ± 4.8 vs. 50.8 ± 5.7 vs. 50.7 ± 5.6 ( p > 0.05)) respectively. Individually, differences were identified; in-season weekly session duration (243 ± 38 min) was higher than during lockdown (180 ± 62 min) ( p < 0.05). During lockdown, weekly MW scores were related to the previous 7-day number of sessions ( r = 0.151) and active min ( r = 0.142) ( p < 0.05). Furthermore, participants that exercised >250 min in lockdown, had higher MW scores (52.46 ± 4.65) than <250 min (50.35 ± 6.55) ( p < 0.05). MW responses to lockdown were best understood on an individual basis. Additionally, PA only had a measurable effect on MW when >250 min. Further, stressors imposed upon players during an EPL season, are potentially greater than those inflicted by the lockdown. Implications for monitoring MW in EPL soccer players and the potential inclusion of an in-season break are discussed. Highlights Mental Wellbeing Responses, as measured by the Warwick-Edinburgh Mental Wellbeing scale did not change significantly at a group level across the four phases of the season. However, on an individual level changes were evident. There was a decline in the trend of wellbeing scores during in-season, return to training and the restart, but an increase in wellbeing scores during lockdown. Physical Activity had a measurable effect on wellbeing, when physical activity was >250 min during lockdown. These findings highlight the need for individual monitoring of wellbeing and longitudinal monitoring in sport to identify decline in wellbeing and implement intervention. In addition, the prescription of physical activity >250 min per week during lockdown in trained athletes may promote positive mental health.